IMPROVING STUDENTSâ WRITING ABILITY THROUGH STORYBOARD - Janah, Miftahul (STKIP Muhammadiyah Pringsewu, 2017)
This study is a classroom action research which intended to improve studentsâ writing ability through Storyboard. The participants were the fourth semester students of English Department of STKIP Muhammadiyah Pringsewu in academic year 2014/ 2015. The instruments used in collecting data were observation, questionnaire, and documents.Â Observation is used to know what is really happening in the class and the condition when the class activity is taking place. Questionnaire is used to know the studentsâ perception towards Storyboard in improving their writing ability, and documents is used to get studentsâ written texts. Then, 1) assembling the data, 2) coding the data, 3) comparing the data, 4) building meanings and interpretations, and 5) reporting the outcomes, are the steps in analyzing the data. Having analyzed the data, it was found that there was improvement of the studentsâ activeness in writing activity and in writing ability.